2011
DOI: 10.1258/acb.2011.011052
|View full text |Cite
|
Sign up to set email alerts
|

Immunoglobulin E deficiency: a forgotten clue pointing to possible immunodeficiency?

Abstract: Background: Patients with primary antibody deficiency often have delayed diagnosis. Very low IgE, found during investigations for allergy, may be a marker for other immunodeficiency. Methods: We introduced a new laboratory policy of testing cases with very low IgE levels for possible linked antibody deficiency. The data represent an audit of routine results collected over two years. Results: Very low IgE ( 2 IU/mL) was identified in 85/2622 (3.2%) routine patient samples. Two children and four adult patients w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
15
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 14 publications
1
15
0
Order By: Relevance
“…These two patients had a diagnosis of bronchiectasis. Our results confirm the investigation by Unsworth and coworkers in their work ‘Immunoglobulin E deficiency: a forgotten clue pointing to possible immunodeficiency?’7 They found very low IgE (≤2 IU/mL) in 85/2622 (3.2%) routine patient samples. Two children and four adult patients were found to have one or more classes of immunoglobulin below the age-specific reference range.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…These two patients had a diagnosis of bronchiectasis. Our results confirm the investigation by Unsworth and coworkers in their work ‘Immunoglobulin E deficiency: a forgotten clue pointing to possible immunodeficiency?’7 They found very low IgE (≤2 IU/mL) in 85/2622 (3.2%) routine patient samples. Two children and four adult patients were found to have one or more classes of immunoglobulin below the age-specific reference range.…”
Section: Discussionsupporting
confidence: 91%
“…Low IgE (<2 kU/L) found during allergy investigations may be a marker for other immunodeficiencies,7 including well defined immune deficiency diseases such as common variable immunodeficiency (CVID), hyper-IgM syndrome, selective IgM deficiency, IgG subclass deficiencies, ataxia telangiectasia and Bruton's or X-linked agammaglobulinaemia (XLA) 1. While Bruton's agammaglobulinaemia and ataxia telangiectasia present in infancy or early childhood, CVID can be diagnosed at any age with no sex preponderance.…”
Section: Introductionmentioning
confidence: 99%
“…These data may suggest a growing importance and high incidence of non-IgE-mediated food allergic disorders in the children studied, accounting for up to 40% of milk protein allergy in infants and young children [22,23] and which manifest as profuse enterocolitis syndrome with diarrhea, repetitive vomiting and failure to thrive or as benign allergic proctocolitis with bloody stools. However, in children with hypogammaglobulinemia, as to isolated or combined immunoglobulin deficiencies, low serum IgE may rather reflect a multiple immunoglobulin deficit and therefore, the role of the non-IgE mediated allergic pathway in this group of immunodeficient children must be particularly emphasized [24,25].…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies found an association between low serum IgE levels and the levels of one or more classes of immunoglobulins (i.e. IgG, IgA and/or IgM) below the reference range for age [10,11]. In line with these reports, a recent review concluded that low IgE levels should be considered as a clinical laboratory 'flag' to screen for antibody deficiency [12].…”
Section: Introductionmentioning
confidence: 92%